2021
DOI: 10.1186/s13023-021-01924-z
|View full text |Cite
|
Sign up to set email alerts
|

Two novel variants in DYRK1B causative of AOMS3: expanding the clinical spectrum

Abstract: Background We investigated pathogenic DYRK1B variants causative of abdominal obesity-metabolic syndrome 3 (AOMS3) in a group of patients originally diagnosed with type 2 diabetes. All DYRK1B exons were analyzed in a sample of 509 unrelated adults with type 2 diabetes and 459 controls, all belonging to the DMS1 SIGMA-cohort (ExAC). We performed in silico analysis on missense variants using Variant Effect Predictor software. To evaluate co-segregation, predicted pathogenic variants were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Notably, the frequency of the risk H1 haplotype in the MEZ population (0.47) was closer to that in the AM population (0.65) than to that in the IBS population (0.13) ( Tables 3 , 4 and Supplementary Tables 1 , 3 ). This finding is in contrast to the relationship observed for alleles harbored on autosomes, which in MEZ usually exhibit intermediate frequencies between AM and IBS ( 31 34 ). We also found that the variants located in TMEM187 (rs2266890 and rs13397) exhibited a significantly decreased LD r 2 value in both the MEZ and AM populations, while the LD r 2 value remained high for all analyzed SNVs in the IBS population ( Figure 1 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the frequency of the risk H1 haplotype in the MEZ population (0.47) was closer to that in the AM population (0.65) than to that in the IBS population (0.13) ( Tables 3 , 4 and Supplementary Tables 1 , 3 ). This finding is in contrast to the relationship observed for alleles harbored on autosomes, which in MEZ usually exhibit intermediate frequencies between AM and IBS ( 31 34 ). We also found that the variants located in TMEM187 (rs2266890 and rs13397) exhibited a significantly decreased LD r 2 value in both the MEZ and AM populations, while the LD r 2 value remained high for all analyzed SNVs in the IBS population ( Figure 1 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We read with great interest the recent article entitled “Two novel variants in DYRK1B causative of AOMS3: expanding the clinical spectrum” by Mendoza-Caamal et al [ 1 ]. Their identification of two novel DYRK1B missense mutations (K68Q and R252H) causative of abdominal obesity metabolic syndrome-3 (AOMS3) provides a long-awaited follow-up to the original discovery of AOMS3 [ 2 ].…”
Section: Dear Editormentioning
confidence: 99%
“… Knockout animal Defects in knockout animal Associated diseases Ref. Lethal at E10.5 to 13.5 19 , 59 , 60 , 61 , 64 , 65 , 69 , 70 Smaller body and hypoplasia of several primitive tissues such as heart, liver, branchial arches, and brain vesicles Dosage-dependent Down syndrome Cerebral hemorrhage and defects in angiogenesis of central arteries in the developing hindbrain DYRK1A-Related Intellectual Disability Syndrome 67 , 68 Hydrocephalus with small brain size and impaired social behavior No obvious developmental defects (Detailed phenotype is not available) Abdominal obesity-metabolic syndrome 3 89 , 90 , 92 Lethal before 72 hpf 98 Shortened and curved body axis, visible loss of somites, and cyclopic eyes Loss of paraxial myoD -expression Lethal at or close to birth Skeletal ciliopathies 109 , 110 Smaller body and hypoplasia of multi organs with especially skeletal abnormality Suppression of Hedgehog signaling via abnormal ciliogenesis Dosage-independent …”
Section: Functions Of Dyrks In Mammalian Development Revealed By ...mentioning
confidence: 99%
“…In humans, DYRK1B mutations are related to abdominal obesity and metabolic syndrome 3 (AOMS3), which is characterized by abdominal obesity, type 2 diabetes, hypertension, and early onset coronary artery disease. 89 , 90 Mutations H90P and R102C affect the structural element DYRK homology box and interfere with the maturation of DYRK1B by tyrosine auto-phosphorylation, thereby compromising the conformational stability of the catalytic domain and resulting in loss-of-function.…”
Section: Functions Of Dyrks In Mammalian Development Revealed By ...mentioning
confidence: 99%